Peran Media Stik Es Krim Dalam Mendukung Pengembangan Literasi Numerasi Anak Usia Dini - A’imatur Riska Nursyafitri; Armiya Nur Lailatul Izzah; Moh Imam Al Ghofiqi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the role of ice cream sticks in supporting the development of numeracy literacy in early childhood at Pertiwi Menden Kradenan Blora Kindergarten. The method used in this study is a qualitative approach with a case study type. Data were collected through observation, interviews, and documentation. The results of this study were carried out in two cycles, namely cycle I and cycle II, which showed significant results and had a positive impact on the development of children's numeracy literacy skills, cognitive skills, helping to stimulate children's fine motor skills, increasing children's concentration, and also helping children solve simple mathematical problems. Although several challenges were still found, such as children's lack of understanding of learning concepts and lack of focus and concentration, learning using ice cream sticks proved to be effective in supporting the development of children's numeracy literacy. This approach is one of the effective strategies for teachers in enlivening the learning atmosphere in the classroom.